Effect of Emotional Intelligence on Organizational Citizenship Behavior with Spirituality Workplace as a Variable Intervening at Guardian in Medan City - Farah Jihan; Ilham Mubaraq Ritonga; Arasy Ayu Setiamy (LLDIKTI Wilayah 1 Sumatera Utara, 2022)
This study aims to determine the effect of emotional intelligence on workplace spirituality. To find out the effect of emotional intelligence and workplace spirituality on organizational citizenship behavior partially. To determine the effect of emotional intelligence on organizational citizenship behavior through workplace spirituality on Guardian Employees in Medan City. The total population in this study amounted to 150 people as a sample using a saturated sampling technique. The analysis technique used is path analysis. The results showed that Emotional intelligence had a significant effect on the workplace spiritually for Guardian Employees. Emotional intelligence has no significant effect on organizational citizenship behavior in Guardian Employees. Workplace spiritually has a significant effect on organizational citizenship behavior in Guardian Employees. There is no significant effect of emotional intelligence on organizational citizenship behavior through workplace spiritually on Guardian Employees